021 Relationships between Cognitive Impairment and Clinical Features of Idiopathic Intracranial Hypertension. (23rd August 2021) - Wang, Wendy; Clough, Meaghan; White, Owen; Shuey, Neil; Walt, Anneke Van der; Fielding, Joanne
Abstract : Objective: To determine whether cognitive impairments in patients with Idiopathic Intracranial Hypertension (IIH) are correlated with changes in visual processing, weight, waist circumference, mood or headache and whether they change over time. Methods: Twenty-two newly diagnosed IIH patients participated, with a subset assessed longitudinally at 3 and 6 months. Both conventional and novel ocular motor tests of cognition were included: Symbol Digit Modalities Test (SDMT), Stroop Colour and Word Test (SCWT), Digit Span, California Verbal Learning Test (CVLT), prosaccade (PS) task, antisaccade (AS) task, interleaved antisaccade-prosaccade (AS-PS) task. Patients also completed headache, mood and visual functioning questionnaires. Results: IIH patients performed more poorly than controls on the SDMT ( p<.001 ), SCWT ( p=.021 ), Digit Span test ( p<0.001 ) and CVLT ( p=.004 ) at baseline, and generated a higher proportion of AS errors in both the AS ( p<.001 ) and AS-PS tasks ( p=.007 ). Further, IIH patients exhibited prolonged latencies on the cognitively complex AS-PS task ( p=.034 ). While weight, waist circumference, headache and mood did not predict performance on any experimental measure, increased retinal nerve fibre layer (RNFL) was associated with AS error rate on both the block ( F(3, 19)=3.22, B=0.30, p=0.022 ) and AS-PS task ( F(3, 20)=2.65, B=0.363, p=0.013 ). Unlike ocular motor changes, impairments revealed on conventional tests of cognition persisted up to 6 months. Conclusions: We found multi-domain cognitive impairments in IIH patients that were unrelated to clinical features. Marked ocular motor inhibitory control deficits were predicted by RNFL thickness but remained distinct from other cognitive changes, underscoring the significance of visual processing changes in IIH.